2022
DOI: 10.1002/solr.202101095
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis‐Free Planar Perovskite Solar Module with 19.1% Efficiency by Interfacial Defects Passivation

Abstract: In few years, perovskite solar devices have reached high efficiency on lab scale cells. Upscaling to module size, effective perovskite recipe and posttreatment are of paramount importance to the breakthrough of the technology. Herein this work, the development of a low‐temperature planar n–i–p perovskite module (11 cm2 aperture area, 91% geometrical fill factor) is reported on, exploiting the defect passivation strategy to achieve an efficiency of 19.1% (2% losses stabilized) with near‐zero hysteresis, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…[2][3][4] Nevertheless, one of the main issues of the perovskite technology is the ability to get both high efficiency and stability also for large area and module-sized devices, with the best PCE values ranging from 19.0% to 22.7% on a mini-module scale using n-i-p structure. [5][6][7][8] With the aim to standardize stability measurements, in 2020 Khenkin et al have reported the assessment of stability tests for perovskite devices, defining the most appropriate protocols to perform, such as ISOS D-1, ISOS T-1, and ISOS L-1, according to which devices were tested for 1000 h under atmospheric conditions, at 85 °C, and under continuous light soaking, respectively. [9] During device fabrication, perovskite formulation and HTM doping are the main actors able to guarantee intrinsic stability over time.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Nevertheless, one of the main issues of the perovskite technology is the ability to get both high efficiency and stability also for large area and module-sized devices, with the best PCE values ranging from 19.0% to 22.7% on a mini-module scale using n-i-p structure. [5][6][7][8] With the aim to standardize stability measurements, in 2020 Khenkin et al have reported the assessment of stability tests for perovskite devices, defining the most appropriate protocols to perform, such as ISOS D-1, ISOS T-1, and ISOS L-1, according to which devices were tested for 1000 h under atmospheric conditions, at 85 °C, and under continuous light soaking, respectively. [9] During device fabrication, perovskite formulation and HTM doping are the main actors able to guarantee intrinsic stability over time.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite properties and stability are still under debate [ 22 , 23 , 24 ]. It is well-known that perovskite grants low fabrication costs because it can be easily processed through precursor solutions with respect to Si or CIGS technologies [ 25 , 26 ]. Despite this, device stability is still an open issue because of the sensitivity of the photoactive material to humidity and micro-structure defects [ 6 , 23 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,16,36–40 ] A layout and interconnection optimization process is thus needed to find the best suitable single cell width according to illumination, sheet resistance, fabrication technology, efficiency, and durability. [ 40–42 ] Finally, sealing of the individual cells in modules is critical, since any sealant failure can severely limit the module lifetime. [ 43 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4,16,[36][37][38][39][40] A layout and interconnection optimization process is thus needed to find the best suitable single cell width according to illumination, sheet resistance, fabrication technology, efficiency, and durability. [40][41][42] Finally, sealing of the individual cells in modules is critical, since any sealant failure can severely limit the module lifetime. [43] In this context, the scaling up from small lab cells to modules and panels by adopting simple and low-cost fabrication processes is of paramount importance, as for other third-generation PV technologies.…”
Section: Introductionmentioning
confidence: 99%